Principales insectos que atacan el grano de fríjol almacenado y su control [conjunto audiotutorial] - Ospina O., Héctor Fabio; Schoonhoven, Aart van; Cardona Mejía, César; García, Jorge E.; Flor Montoya, Carlos A. (International Center for Tropical Agriculture, 1979)
This audiotutorial unit (cassette, printed script, 140 color slides, study guide, self-evaluation test), prepared by the Communication Support Unit at CIAT, is available for use with a manually or automatically synchronized slide projector/cassette tape recorder. Each unit is available from the Distribution Office at a cost of US$50; photocopies of the study guide alone can be obtained from the Bean Information Center. The control of insects attacking stored beans is of great importance since they not only cause losses in quantity and quality but can also increase the incidence of secondary attack by fungal and bacterial microorganisms. Information is given on the economic importance, type of damage caused, biology, control measures for small- and large-scale operations, and methodology of investigation (rearing the bruchids in the lab and parameters to be considered) for the 2 most important bruchid pests: Zabrotes subfasciatus and Acanthoscelides obtectus. (CIAT)